The problem of intertext in the kazakh word art (Eurasian Journal of Philology Science and Education, 2016)
The article considers the problem of intertextuality revealed in the process of analysis of the literary text. The author explores the intertextual connections of Kazakh prose, poetry, oral individual literature with folklore basis. The article presents a broad overview of the works of such famous foreign researchers, who were at the origins the theory of intertextuality, as M. Yampolsky, I. Arnold, M. Bakhtin, Umberto Eco, J. Zhennet, J. Kristeva, Y. Tynyanov, Ferdinand de Saussure, G. Denisova, Y. Lotman, M. Gasparov. In the works of national literature intertextual relations are traced mainly through the prism of traditional continuity or examples of the Nazir genre. Therefore, in this article, the author decided to fill this gap. From this perspective, it reveals the artistic functions of intertextual relations in various samples of Kazakh literature, their deep national identity in the structure of a work of art. Building on the existing in small quantities works of Kazakh literary scholars, and mostly – on the works of Western and Russian theorists of intertextuality, the author analyzes the function of intertextuality in the individual oral poetry, in oratorical folk art, written literature and poetry of zhyrau.
Keywords: problem of intertext; intertextuality; folklore; poetry of priest akyns; bi-speaker; traditional oratorical speeches; author’s oral lit¬erature; oratorical speech; art of the word.